Antibacterial activity of monoacetylated alkyl gallates against Xanthomonas citri subsp citri - Savietto, Abigail [UNESP]; Polaquini, Carlos Roberto [UNESP]; Kopacz, Malgorzata; Scheffers, Dirk-Jan; Marques, Beatriz Carvalho [UNESP]; Regasini, Luis Octavio [UNESP]; Ferreira, Henrique [UNESP] (Springer, 2018)
Asiatic citrus canker (ACC) is an incurable disease of citrus plants caused by the Gram-negative bacterium Xanthomonas citri subsp. citri (X. citri). It affects all the commercially important citrus varieties in the major orange producing areas around the world. Control of the pathogen requires recurrent sprays of copper formulations that accumulate in soil and water reservoirs. Here, we describe the improvement of the alkyl gallates, which are potent anti-X. citri compounds, intended to be used as alternatives to copper in the control of ACC. Acetylation of alkyl gallates increased their lipophilicity, which resulted in potentiation of the antibacterial activity. X. citri exposed to the acetylated compounds exhibited increased cell length that is consistent with the disruption of the cell division apparatus. Finally, we show that inhibition of cell division is an indirect effect that seemed to be caused by membrane permeabilization, which is apparently the primary target of the acetylated alkyl gallates.
Keywords: Citrus canker; Gallic acid; Cell division; Membrane disruption